Avaliação do Programa Criança Feliz: uma análise quantitativa sob a percepção dos cuidadores na região do meio norte do Piauí - Carvalho, Aline Kárem Santos (2023)
The Happy Child program (PCF) was created to reinforce the implementation of the Legal Framework for Early Childhood and seeks to contribute to breaking the cycle of poverty, reducing violence and reducing school dropout rates, aiming to promote the integral development of children in early childhood. However, the effectiveness of the program is one of the biggest questions surrounding public policies for early childhood in Brazil. Therefore, the objective of the study is to evaluate the perception of caregivers of children using the Criança Feliz Program regarding the activities and results of the program in Meio Norte Piauí. To this end, 283 questionnaires were administered in three municipalities in the north of Piauí, which were analyzed using descriptive statistics and factor analysis. The main results reveal the predominance of female caregivers and mothers, with an intermediate educational level, with employment and salary seasonality that leads to financial dependence on government programs. The factor analysis resulted in six constructs, namely: Readiness of the Happy Child Program and visitors; Tangibility of playful materials; Visitor empathy and trustworthiness; PCF safety and results; Tangibility of informative materials and satisfaction with the Criança Feliz Program. Through the results, it is concluded that in general, caregivers are satisfied with the PCF's activities, the most positive perceptions are included in the Empathy and Reliability dimension of the visitor, while, Readiness of the PCF and visitors has a lower average. Regarding the degree of satisfaction of caregivers in each municipality with their programs, they showed that they were completely satisfied with the PCF's activities. When evaluating the level of general satisfaction of caregivers regarding the results of the Criança Feliz Program, a positive evaluation was found. In this area, the results obtained from a general perspective do not demonstrate discrepancies between the opinions of caregivers from the three municipalities, both the average and median results are relatively similar between the three, demonstrating that both have managed to satisfy users of the Happy Child program. Such data reflect the similarity between the municipalities, a fact that can be justified by the geographic proximity, economic, cultural and social characteristics of the region studied. Furthermore, it is expected that the results can contribute to scientific advances on the topic, by resulting in an instrument for evaluating the satisfaction of caregivers in the Criança Feliz program, which can be used by participating municipalities and the Ministry of Citizenship. In view of this, the investigation into the satisfaction of families using the Criança Feliz Program can represent for the managers themselves a current panorama of how the program's activities are compared to its beneficiary agents.